Determinants Compliance of Rubber Farmer for Paying Contributions Independent Health BPJS in Muaro Jambi Regency - Nur Octaviani; Dwi Noerjoedianto; Arnild Augina Mekarisce (CV. AFDIFAL MAJU BERKAH, 2022)
The National Health Insurance Program organized by the Social Security Administering Body (BPJS) in accordance with the provisions of Law Number 24 of 2011 which is a government program is useful to support deterministic and comprehensive health insurance for all Indonesian people so that Indonesian people can live healthy, productive, and prosperous. It was also recorded for the number of BPJS membership per segment on September 30 in Jambi Province, as many as 2,637,537 people who became BPJS participants with a percentage of 74.66%, with a total of 641,323 PBPU Mandiri members. Based on data from BPJS Jambi City, the data in arrears in 2019 in Muaro Jambi Regency as a whole is 60.3%. The purpose of this study was to obtain an overview of the determinants of rubber farmer compliance in paying BPJS health contributions independently in Muaro Jambi in 2021. This study used a cross-sectional method, with a population of 75,437 and a sample of 106. In this study, bivariate analysis used the chi test. -square. The results of this study indicate that there is no relationship between the knowledge variable and the number of family members with the compliance of rubber farmers in paying independent health BPJS contributions, while there is a relationship between income variables, distance of payment places and perceptions with rubber farmers' compliance in paying BPJS independent health contributions.